2018
DOI: 10.14419/ijet.v7i3.15.17403
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Stock Market Index Using Hybrid Intelligence Model

Abstract: Predicting financial market changes is an important issue in time series analysis, receiving an increasing attention due to financial crisis. Autoregressive integrated moving average (ARIMA) model has been one of the most widely used linear models in time series forecasting but ARIMA model cannot capture nonlinear patterns easily. Generalized autoregressive conditional heteroscedasticity (GARCH) model applied understanding of volatility depending to the estimation of previous forecast error and current volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They also compare the results with the LSTM and RF models, where the proposed model outperforms other methods. [39] WT-SAEs-LSTM Financial Time Series Stock Price Prediction Shekhar and Varshney [66] GA-SVM Financial Time Series Stock Price Prediction Ahmadi et al [67] ICA-SVM Financial Time Series Stock Price Prediction Ebadati and Mortazavi [68] GA-ANN Financial Time Series Stock Price Prediction Johari et al [69] GARCH-SVM Financial Time Series Stock Price Prediction…”
Section: Lstmmentioning
confidence: 99%
See 1 more Smart Citation
“…They also compare the results with the LSTM and RF models, where the proposed model outperforms other methods. [39] WT-SAEs-LSTM Financial Time Series Stock Price Prediction Shekhar and Varshney [66] GA-SVM Financial Time Series Stock Price Prediction Ahmadi et al [67] ICA-SVM Financial Time Series Stock Price Prediction Ebadati and Mortazavi [68] GA-ANN Financial Time Series Stock Price Prediction Johari et al [69] GARCH-SVM Financial Time Series Stock Price Prediction…”
Section: Lstmmentioning
confidence: 99%
“…Their study suggests that this hybrid machine learning model has an improved sum square error (SSE) (i.e., performance accuracy) by 99.99% and improved time (i.e., speed accuracy) by 90.66%. Johari et al [69] compared the accuracy and performance of GARCH-SVM and GARCH-ANN models in the financial time series data for stock price forecasting. They found that GARCH-SVM outperformed GARCH-ANN, SVM, ANN, and GARCH based on MSE and RMSE accuracy metrics.…”
Section: Other Algorithmsmentioning
confidence: 99%